2017
DOI: 10.1007/s40257-017-0278-9
|View full text |Cite
|
Sign up to set email alerts
|

Primary Localized Cutaneous Amyloidosis: A Systematic Treatment Review

Abstract: No definitive recommendation of preferable treatment procedures can be made based on the analyzed literature. Randomized controlled trials are needed to offer patients an evidence-based therapy with high-quality standardized treatment regimens for PLCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
129
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(152 citation statements)
references
References 88 publications
2
129
0
8
Order By: Relevance
“…Authors had listed several side effects for topical DMSO including contact urticaria, desquamation, burning sensation, and garlic‐like breath odor mostly in the high concentration use . In the present study, no adverse reaction was observed on both sides.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Authors had listed several side effects for topical DMSO including contact urticaria, desquamation, burning sensation, and garlic‐like breath odor mostly in the high concentration use . In the present study, no adverse reaction was observed on both sides.…”
Section: Discussionsupporting
confidence: 47%
“…Topical DMSO 10% to 100% solution is traditionally used to treat macular amyloidosis and lichen amyloidosis. Most of the publications showed promising outcomes within relatively short treatment period, and all of them reported an early reduction in pruritus, without regression of amyloid deposits . Only four studies with acceptable case numbers could be found in the literature .…”
Section: Discussionmentioning
confidence: 99%
“…Localized amyloidosis occurs in a variety of organ systems, including the skin and nails [35], larynx [36], lung [37] bowel [38], orbit [39], or urinary tract [40], including the renal pelvis, ureter, bladder, and urethra. Evolution of localized amyloidosis to systemic amyloidosis is rare [37].…”
Section: Localized Versus Systemic Amyloidosismentioning
confidence: 99%
“…Unfortunately, standardised treatment guidelines have not been established because of a lack of randomised control trials. 11 complaints of intense pruritus and the clinical appearance of the eruption. Long-term periodic follow-up is required as recurrence is common.…”
Section: Answermentioning
confidence: 99%